O lugar de morar: estado, igreja e moradores na produção da habitação popular em Belo Horizonte (o Bairro Dom Cabral, 1959/1981) - Carla Ferretti Santiago (1999)
This work has the purpose to analyse the production of the space of popular house in Belo Horizonte. For this reason, the residential section Dom Cabral was chosen, in the west part of the city, as a main reason, seeking, from the studies of the history of that residential section, its conception and occupation, giving a view of that major question. At the same time, the analysis of the trajectory of the residential section, around the ending of the 1950s and the beginning of the 80s, enables to understand the perfomance of the three fellows facing the problem of the popular homes, as well as to estimate its insertion in the building of this place in the city: the state public power, the Catholic Church, and the inhabitants themselves of the Dom Cabral residential section.